Desain dan Evaluasi Kinerja Sistem Kendali Otomasi Air Kolam Pembibitan Lele (Clarias sp.) - Desrial, Desrial; Yahya Abdul Kodir, Delphi Yahya (Jurnal Agricultural Biosystem Engineering, 2024)
Catfish nurseries are required to be able to see the appropriate needs for catfish larvae, especially in pond water quality. However, in its application, generally adjustments to the needs of water quality are only carried out without any special treatment, so that the survival obtained is still low. The purpose of this research is to make a machine that can control the quality of catfish breeding water, test the performance of the machine and the effect of its use. This study used the method of formulating and evaluating the design and testing the performance of the machine which consisted of several stages, including: formulating and evaluating the design, manufacturing the machine, functional testing, performance testing, and the influence of the machine performance. The results obtained after testing were the performance of the machine affecting the speed of hatching eggs, the growth rate and survival of catfish larvae. The speed of hatching catfish eggs is 4 hours faster using a machine. The growth rate using a machine is 0.061g/head, while without using a machine it is 0.053g/head. The survival of fish larvae using machine was 80.3%, while without using machine was 63.1%. Keywords: Control, Fish Larvae, Growth Survival, Water Quality.